Maximizing Teacher and Student Potential in the Language Classroom - Siregar, Nujuluddin; Kartono, -; Gufron, Uup (STKIP PGRI Tulungagung, 2025)
In traditional classrooms, activities and tasks were clearly a part of a pre-planned syllabus that had been previously designed and based on specific curriculum guidelines. Teachers, in answering the prescriptions laid down by these guidelines have found a difficult to be creative given the time and the demands imposed by them. In responding to admonitions for them to be creative, teachers have often resorted to bringing in randomly selected task for the sake of variety and to avoid monotony. In a learner-centered curriculum, learning tasks are selected for the purpose of raising learner awareness and development of strategies while at the same time working on items in the language that would lead to better fluency.